2019
DOI: 10.1002/hed.26007
|View full text |Cite
|
Sign up to set email alerts
|

Management of unilateral head and neck carcinoma of unknown primary: Retrospective analysis of the impact of postoperative radiotherapy target volumes

Abstract: Background: We compared the outcome of postoperative unilateral cervical nodes radiotherapy (UL-RT) vs bilateral cervical nodes plus total mucosal irradiation (COMP-RT) in the management of head and neck carcinoma of unknown primary (HNCUP).Methods: HNCUP, defined by the absence of primary despite a PET-CT combined with a panendoscopy, were treated with curative intent by initial ipsilateral neck dissection. Sixty-nine patients with unilateral HNCUP were included: 23 received UL-RT while 46 received COMP-RT. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…We found that local recurrences occurred in all cases on the initially affected side of the neck, and in 85 % in the former CTV. This is comparable to other studies showing none [31] , [32] , [33] , [34] , [35] or only a single [10] , [27] , [36] contralateral recurrence among the unilaterally irradiated patients. Some older cohorts form the 2D era describe higher rates of contralateral recurrences from 10 % up to 15.6 % [8] , [26] , [37] .…”
Section: Discussionsupporting
confidence: 90%
“…We found that local recurrences occurred in all cases on the initially affected side of the neck, and in 85 % in the former CTV. This is comparable to other studies showing none [31] , [32] , [33] , [34] , [35] or only a single [10] , [27] , [36] contralateral recurrence among the unilaterally irradiated patients. Some older cohorts form the 2D era describe higher rates of contralateral recurrences from 10 % up to 15.6 % [8] , [26] , [37] .…”
Section: Discussionsupporting
confidence: 90%
“…In a French study published in 2020, Podeur et al, 13 compared the outcomes of post‐operative unilateral cervical nodal radiotherapy ( n = 23) against post‐operative bilateral cervical nodal plus total mucosal radiation ( n = 44). All patients underwent neck dissection.…”
Section: Resultsmentioning
confidence: 99%
“…Podeur et al 13 also provided information on acute and late toxicity and QOL measures in patients treated with unilateral or bilateral post‐operative neck radiotherapy. The incidences of grade ≥2 radiation dermatitis were similar (48% vs. 46%, p = 1.00) but there was greater grade ≥2 mucositis (44% vs. 59%, p = .31) and weight loss >4 kg (26% vs. 48%, p = .12) in patients treated with bilateral radiotherapy; however, this difference was not significant.…”
Section: Resultsmentioning
confidence: 99%